ANALISIS MANAJEMEN SYARIAH PERBANDINGAN RASIO UTANG ATAU PINJAMAN LUAR NEGERI TERHADAP PRODUK DOMESTIK BRUTO NEGARA REPUBLIK INDONESIA MASA PEMERINTAHAN SUSILO BAMBANG YUDHOYONO TAHUN 2005–2012, DENGAN MASA PEMERINTAHAN JOKO WIDODO TAHUN 2015—2022 - Ma’arif, Muhamad Syamsul; Thantawi, Tubagus Rifqy; Melinasari, Susi (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
This research aims to determine the comparison of debt to gross domestic product of the Republic of Indonesia during the 2005-2012 administration of Susilo Bambang Yudhoyono, with the 2015-2022 administration period of Joko Widodo. The variables studied consist of two variables, namely the independent variable and the dependent variable. The objects and data in this research are the ratio of foreign debt or loans and gross domestic product of the Republic of Indonesia during the 2005-2012 Susilo Bambang Yudhoyono administration, with the 2015-2022 Joko Widodo administration. This study uses a quantitative approach. Data collection method in the form of official documents from Bank Indonesia (BI), Central Statistics Agency (BPS), and other official documents. Using secondary data, then processed using the IBM Statistical Program for Social Sciences (SPSS) software version 25, with the Independent Sample T-Test data analysis method. The results of this research show that the average value of the Ratio of Debt or Foreign Loans to Gross Domestic Product of the Republic of Indonesia during the Susilo Bambang Yudhoyono Administration in 2005-2012 was higher than during the Joko Widodo Administration in 2015-2022. There is a relationship and difference between the Ratio of Debt or Foreign Loans to the Gross Domestic Product of the Republic of Indonesia during the 2005-2012 Government of Susilo Bambang Yudhoyono, and the 2015-2022 Government of Joko Widodo. In sharia management, debt is permitted with the principle that if the government has difficulty obtaining funds, it must not be beyond its capabilities (ghalabtid dayn), and the State must intend and make a strong effort to pay it and if it owes money to another party within a certain period of time, then it should record it.